Validation of a Didactic Model for the Understanding of Academic Texts in Virtual Higher Education - Rodríguez, Maira Alejandra Pulgarín (International Journal of Emerging Technologies in Learning (iJET), 2023)
Academic literacy is a crucial aspect of education, yet assessing it remains a challenge for universities in knowledge management. This research focuses on how to support Colombian university students in understanding academic texts in virtual learning environments. To address this issue and fill a gap in the literature, the main objective of this study is to propose a model for assessing academic literacy in virtual learning environments, using the Delphi method as a validation tool. A panel of language experts from various Latin American countries was convened to ensure a diverse and representative perspective of the region for this study. The research involved the participation of 15 experts with doctoral degrees from different countries, which allowed for a broad and heterogeneous perspective on academic literacy in virtual learning contexts in Latin America. Each of the participants contributed their knowledge and experience in the language area. In the results, ten key elements were identified and distributed in different subconstructs that allow for a comprehensive evaluation and improvement of academic competence in virtual learning environments. The identification of these elements provides teachers and university management personnel with a reliable and precise tool for evaluating students’ competence levels in virtual learning environments and designing effective pedagogical strategies to improve their academic performance.